Mechanisms of Flucytosine Resistance in Cryptococcus gattii May Be Independent of the FCY2-FCY1-FUR1 Pathway. (4th October 2017) - Vu, Kiem; Thompson, George R; Roe, Chandler; Sykes, Jane; Dreibe, Elizabeth; Lockhart, Shawn; Meyer, Wieland; Engelthaler, David M; Gelli, Angie
Abstract: Background: Cryptococcosis is an opportunistic fungal infection caused by both Cryptococcus neoformans and its sibling species, Cryptococcus gattii. Flucytosine (5FC) is one of the most widely used antifungals against Cryptococcus spp., yet very few studies have looked at the molecular mechanisms responsible for 5FC resistance in this pathogen. Methods: Eleven Cryptococcus gattii clinical isolates were selected based on differential 5FC susceptibility. All isolates underwent whole-genome sequencing and genomic differences in key genes involved in flucytosine metabolism were examined. Heterologous expression of FCY1 and spot sensitivity assays were performed to examine regions of interest based on genomic differences. Results: Susceptibility assays and sequencing analysis revealed an association between a point mutation in cytosine deaminase (FCY1) and 5FC resistance in two C. gattii clinical isolates, B9322 and JS5. This mutation results in the replacement of arginine for histidine at position 29 and occurs within an unconserved stretch of amino acids. Heterologous expression of FCY1 and spot sensitivity assays demonstrate that the point mutation did not have any effect on FCY1 activities and was not responsible for 5FC resistance. Comparative sequence analysis further show that no amino acid changes were observed in either cytosine permeases (FCY2-4) or uracil phosphoribosyltransferase (UPRTase, encoded by FUR1) among 5FC resistant and 5FC susceptible C. gattii isolates. Conclusion: Together, our work suggests that the mediator(s) of 5FC resistance in B9322 and JS5 is likely found either downstream of FUR1 or on disparate regulatory pathways that modulate flucytosine metabolism. These findings suggest clinical 5FC resistance in C. gattii may occur by a nontraditional mechanism(s). Disclosures: All authors: No reported disclosures.